2016
DOI: 10.1002/eji.201646553
|View full text |Cite
|
Sign up to set email alerts
|

A novel Foxn1eGFP/+ mouse model identifies Bmp4‐induced maintenance of Foxn1 expression and thymic epithelial progenitor populations

Abstract: Although forkhead-box n1 (Foxn1) is a critical thymic epithelial cell regulator in thymus organogenesis, its association with epithelial differentiation and homeostasis in the postnatal and aged thymic microenvironment remains conflicting. Consequently, we have generated a Foxn1 knock-in mouse model that allows for refined investigation of the aging thymic epithelium. This reporter line differs from those previously published in that concomitant expression of enhanced green fluorescent protein enables live cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 46 publications
(111 reference statements)
2
30
0
Order By: Relevance
“…The post-pubertal increase in Bmp4 expression by supporting stromal cells was, however, greater in females, and implicates better progenitor maintenance. Its receptor, Bmpr2, is primarily expressed on cTEC lo and mTEC lo progenitors (42), and was proposed to have a role in maintaining progenitor populations at the expense of differentiation (10). However, Bmp4 induced self-renewal of progenitors may also have a role in thymus regeneration following damage, as demonstrated following irradiation (43).…”
Section: Discussionmentioning
confidence: 99%
“…The post-pubertal increase in Bmp4 expression by supporting stromal cells was, however, greater in females, and implicates better progenitor maintenance. Its receptor, Bmpr2, is primarily expressed on cTEC lo and mTEC lo progenitors (42), and was proposed to have a role in maintaining progenitor populations at the expense of differentiation (10). However, Bmp4 induced self-renewal of progenitors may also have a role in thymus regeneration following damage, as demonstrated following irradiation (43).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, endogenous regeneration following thymic damage was shown to involve TEC stimulation by endothelial cell-derived BMP4, which subsequently increased FOXN1 expression (Wertheimer et al, 2018). TEC expression of the BMP4 receptor BMPR2 was predominantly in TEPCs, Sca-1 lo cTEC lo precursors, and mTEC lo precursors of 7-week-old mice (Barsanti et al, 2017). Although the majority of BMP4 production in the adult thymus is derived from fibroblasts and endothelial cells (Barsanti et al, 2017), in addition to an increase in fibroblast BMP4 expression with aging, we identified increased BMP4 expression by TECs ( Figure 3F).…”
Section: Reduction In Medullary Epithelia and Tepc Differentiation Wimentioning
confidence: 86%
“…We have previously shown that BMP4 supplementation of in vitro 3D postnatal TEC cultures maintained cTEC lo and mTEC lo precursors at the expense of differentiation into their mature counterparts (Barsanti et al, 2017). Furthermore, endogenous regeneration following thymic damage was shown to involve TEC stimulation by endothelial cell-derived BMP4, which subsequently increased FOXN1 expression (Wertheimer et al, 2018).…”
Section: Reduction In Medullary Epithelia and Tepc Differentiation Wimentioning
confidence: 98%
“…Transgenic expression of Noggin under the control of a FoxN1 promoter leads to a hypoplastic spheric thymus always containing big cystic structures [125]. These structural alterations seem to be the result of a branching defect in consonance with the known role of BMP signaling in regulating branching morphogenesis of different organs [26] and to affect Foxn1 expression [147]. Figure 2.…”
Section: After Acquisition Of Thymus Fate Thymic Primordium Undergoementioning
confidence: 98%